PERFORMA PELELEHAN ES PADA BENTUK ES YANG BERBEDA (Performance of Diffrent Ice-Forms Melting Process) - Aprilia Putri Kusumah; Yopi Novita; Deni A. Soeboer (Marine Fisheries: Jurnal Teknologi dan Manajemen Perikanan Laut, 2016)
ABSTRACT Ice as a cooling medium in the handling of fresh fish is widely used. Information about the rate of temperature change and the rate of melting of ice in the fish storage box is not available. Therefore, this research needs to be conducted to determine the ability of different forms of ice to decrease the temperature of the ice box where they are placed. The objectives of this research are to calculate the rate of ice melting and the rate of temperature change in the box that contains the bulk ice and crushed ice, and compare the ability of bulk ice and crushed ice to cool temperature inside the storage box fish. Experimental method was applied in this research, which data collection consisted of a total volume of ice melted and the temperature in the box per unit time. The research results showed that the bulk ice has the ability to cool the space they occupy much faster when compared with crushed ice. In addition, bulk ice melt faster when compared with crushed ice.